Uninterruptible power supplies - Platts, John; St. Aubyn, John (Energy Engineering., 1992)
Valuable data, essential services and production process plants are typical assets that can be lost or seriously disturbed by power supply breaks or contamination. An uninterruptible power supply (UPS) can avoid potentially catastrophic havoc caused by electricity supply line disturbances. Behind this protection, however, is the need for a sound UPS design based on a thorough specification to achieve reliable and consistent functioning. This book is a comprehensive guide to the various types of UPS systems available and how they may be specified and applied effectively. It should be beneficial to design engineers working on commercial premises and industrial processes, that employ sensitive electronic equipment; to building services and their consulting engineers; and to facilities managers concerned with computer installations and telecommunications systems. Essentially written for practising electrical engineers, the text will also be of value to students in computer technology and telecommunications as well as building services and design.